ЭЛЕКТРОННЫЙ МЕТОДИЧЕСКИЙ АППАРАТ ПРЕДМЕТИЗАТОРА В ГПНТБ СО РАН (Библиосфера, 2010)
The formation of rules and methodical instrument for a subject cataloger began in SPSTL SB RAS in 2007. The authors describe the structure, functions and technology of operating the electronic file of methodical decisions on subject cataloging. The role and aims of authority file «Subject headings» are considered, as well as the the process of its creation.